Fuel Wood and Forest Management: A Strategy for Agricultural Sustainability in Benue South, Nigeria - Shamsu Abdullahi Idris; Nura Saleh (CV Media Inti Teknologi, 2026)
Background of study: Deforestation driven by fuel wood extraction has become a major environmental challenge in many developing countries, including Nigeria. Excessive dependence on forest resources contributes to land degradation, soil fertility loss, and reduced agricultural productivity. In rural communities, forests play a crucial role in sustaining agricultural systems, supporting livelihoods, and maintaining ecological balance. Aims and scope of paper: This study examines the relationship between fuel wood utilization, forest management practices, and agricultural sustainability in Benue South Senatorial District, Nigeria. Methods: The study was conducted across five Local Government Areas (Agatu, Apa, Otukpo, Ador, and Obi). A purposive sampling technique was used to distribute 790 questionnaires, of which 729 were returned and analyzed, representing a 92.4% response rate. Data were collected through questionnaires, Focus Group Discussions (FGDs), and Key Informant Interviews (KIIs). Descriptive statistics, including frequency and percentage, were applied, while the Relative Importance Index (RII) was used to evaluate the perceived impact of deforestation on agricultural practices. Result: The findings indicate that most respondents were farmers and long-term residents of the study area. A significant proportion (71%) were aware of the negative effects of deforestation on agriculture. The results also highlight several adaptive strategies adopted by communities, including alternative fuel sources, improved forest management practices, and increased environmental awareness. Conclusion: Effective forest management and reduced dependence on fuel wood are essential for promoting sustainable agricultural development. Strengthening community awareness, encouraging alternative energy sources, and implementing sustainable forestry policies are critical steps toward ensuring agricultural sustainability in the region.